Community empowerment in making ecobricks to overcome the problem of plastic waste - Rofiqotul Ngafiyah; Annisa Fajar Rahmawati; Dita Noviyanti; Teni Okty Handayani; Agus Fatkhurrohman; Nurul Ariffudin; Isna Putri Utami; Miftah Parasasmi; Fera Indriansyah; Raeza Pradeka Rahmawati; Moh Salimi (Universitas Pendidikan Indonesia, 2024)
Ecobricks is an innovation that produces a product made from plastic bottles filled with compacted plastic waste, which has not yet been attempted to be created on a large scale. The target of this activity is all PKK women in Adikarso Village. The implementation method carried out by socialization or counseling begins with a survey of the plastic waste problem. There is a need to utilize plastic waste in a product with use value. This training aims to increase residents' understanding of the use of plastic waste in ecobrick products. This activity began with outreach, collecting plastic waste, and preparing tools and materials, followed by training activities with direct practice in making ecobricks. Data collection techniques were carried out using observation and questionnaires. The results of this training include ecobrick products and increasing residents' understanding of the use of plastic waste. First, plastic waste is used to make ecobrick products, namely garden chairs. Second, residents' understanding is related to knowledge about plastic waste and ecobrick products. Based on these results, community empowerment impacts residents' knowledge regarding the use of plastic waste in ecobrick products that have use value and can generate income for the residents of Adikarso Village. Abstrak Ecobrick merupakan suatu inovasi untuk menghasilkan suatu produk yang terbuat dari botol plastik yang diisi sampah plastik yang dipadatkan yang secara luas belum diupayakan untuk diproduksi secara besar-besaran. Sasaran dari kegiatan ini adalah seluruh ibu-ibu PKK Desa Adikarso dengan metode pelaksanaan dilakukan dengan sosialisasi atau penyuluhan yang diawali dengan survei permasalahan sampah plastik. Perlu adanya pemanfaatan sampah plastik menjadi sebuah produk yang memiliki nilai guna. Tujuan pelatihan ini adalah meningkatkan pemahaman warga mengenai pemanfaatan sampah plastik menjadi produk ecobrick. Kegiatan ini dimulai dengan melakukan sosialisasi, pengumpulan sampah plastik, persiapan alat dan bahan, dilanjutkan kegiatan pelatihan dengan praktek langsung pembuatan ecobrick. Teknik pengumpulan data dilakukan dengan observasi dan angket. Hasil dari pelatihan ini meliputi produk ecobrick dan peningkatan pemahaman warga mengenai pemanfaatan sampah plastik. Pertama, sampah plastik dimanfaatkan menjadi produk ecobrick yaitu kursi taman. Kedua pemahaman warga terkait pengetahuan tentang sampah plastik dan pengetahuan tentang produk ecobrick. Berdasarkan hasil tersebut, maka pemberdayaan masyarakat berdampak pada pemahaman warga terkait pemanfaatan sampah plastik menjadi produk ecobrick yang memiliki nilai guna dan dapat menghasilkan sumber pendapatan bagi warga Desa Adikarso. Kata Kunci: ecobricks; pelatihan; pemberdayaan masyarakat; sampah plastik